2020
DOI: 10.4081/jphr.2020.1986
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sars-Cov-2 Infection through Rapid Serology Testing in the Homeless Population in the City of Rome, Italy. Preliminary Results

Abstract: Background: The development of COVID-19 pandemic has affected all segments of the population; however, it had a significant impact on vulnerable subjects, such as in people experiencing homelessness. The aim of this study was to evaluate the prevalence of COVID-19 spread in homeless persons in the city of Rome, Italy.  Design and Methods: Patients included in the study underwent a clinical evaluation and rapid antibody analysis on capillary blood for the presence of immunoglobulin G (IgG) and immunoglobulin M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
“…A number of included studies reported infection attack rates of SARS-CoV-2 among study participants: 29 studies measured positivity rates (i.e., current infection) [ 13 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], seven measured seroprevalence (i.e., prevalence of antibodies for SARS-CoV-2, indicating historic infection) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and four measured both positivity and seroprevalence rates [ 68 , 69 , 70 , 71 ]. Additionally, data regarding SARS-CoV-2 symptoms reported by study participants were provided by 32 articles [ 7 , 8 , 33 , 34 , 35 , 36 , 38 , 42 , 45 , 46 , …”
Section: Resultsmentioning
confidence: 99%
“…19 quantitative studies were conducted in the USA [23À41], three in Canada [42À44],three in France [16,45,46], two in Italy [47,48], and one in Belgium [49], Spain [50], Slovakia [51], and Denmark [52], respectively. The data collection period considering all studies ranged from January 2020 to October 2020.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of IPC strategies, 11 studies [29,31,35,37,39,42,47,48,54,56,57] discussed comprehensive and rapid testing including collaboration with regional laboratories for quick turnaround of positive tests, expansion of non-congregate housing and individual strategies in the shelters, e.g. spacing between beds and limited staff rotation, as critical measures to be taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, the primary healthcare services of the [ blinded ], Vatican City, offered a SARS-CoV-2 infection control service for persons experiencing homelessness through nasopharyngeal swab tests and prevention measures [ 2 , 3 ]. Tests were performed in all homeless patients presenting to these facilities seeking general medical care over a period of 16 months.…”
mentioning
confidence: 99%